Pengembangan Komik Digital Interaktif sebagai Media Pembelajaran Pendidikan Jasmani, Olahraga dan Kesehatan pada Materi Pencak Silat di SD Kota Pekanbaru - Na’imatul Rodiah; Ramadi, Ramadi; Vai, Aref (Jurnal Porkes, 2024)
This study aims to evaluate the feasibility of interactive digital comics as a learning media for PJOK on pencak silat material at SDN 37 Pekanbaru City. This research method uses a development model (analysis, design, development, implementation, evaluation). Field trial subjects were carried out in a small group test with 15 fifth grade students. The feasibility assessment of digital comics was carried out by material experts, media experts, and through student responses. The results of the study obtained an average material expert validation score of 3.72 and a media expert of 3.46. Material experts assess the content of the material in digital comics as adequate, although there are shortcomings in the linguistic and presentation aspects that need to be improved. Meanwhile, media experts gave a positive assessment of the simplicity, integration, color, and arrangement of digital comics, but there were deficiencies in the aspects of language and text. The response of students was very positive, with students' interest reaching 91.2% and understanding of the material reaching 91.4%. This study concludes that the development of interactive digital comics as PJOK learning media has obtained good validation from experts. The implication of this research is that interactive digital comics have great potential as an effective learning tool in schools.